2011
DOI: 10.1242/jcs.062307
|View full text |Cite
|
Sign up to set email alerts
|

ERBIN is a new SARA-interacting protein: competition between SARA and SMAD2 and SMAD3 for binding to ERBIN

Abstract: Summary SARA, an early endosomal protein, plays a key role in TGFb signalling, as it presents SMAD2 and SMAD3 for phosphorylation by the activated TGFb receptors. Here, we show that ERBIN is a new SARA-interacting protein that can be recruited by SARA to early endosomes. ERBIN was recently shown to bind and segregate phosphorylated SMAD2 and SMAD3 (SMAD2/3) in the cytoplasm, thereby inhibiting SMAD2/3-dependent transcription. SARA binds to ERBIN using a new domain, which we have called the ERBID (ERBIN-binding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 51 publications
0
24
0
Order By: Relevance
“…interact with SHOC2 and SMAD3, respectively (22,23,40). A truncation of DSG1 lacking the unique PL, RUD, and TD regions, though capable of mediating previously mapped interactions with Pg (41), failed to bind Erbin.…”
Section: Figurementioning
confidence: 90%
“…interact with SHOC2 and SMAD3, respectively (22,23,40). A truncation of DSG1 lacking the unique PL, RUD, and TD regions, though capable of mediating previously mapped interactions with Pg (41), failed to bind Erbin.…”
Section: Figurementioning
confidence: 90%
“…Like TMEPAI, its homolog C18 ORF1 can also interfere with the interaction of Smad2 and Smad3 with SARA and, thus, attenuates Smad recruitment to TβRI (Nakano et al 2014). Similarly, ERBIN (ERBB2/HER2-interacting protein), a SARA-interacting protein, inhibits TGF-β signaling by competing with SARA for the association with Smad2 and Smad3 and inhibiting their activation (Sflomos et al 2011). Although all of these studies support the role of SARA in promoting TGF-β signaling, it was reported that silencing SARA expression using small interfering RNA (siRNA) has no effect on TGF-β signaling in HeLa cells (Bakkebo et al 2012), which might be caused by incomplete down-regulation of SARA expression and/or a redundant functions of Hrs/Hgs.…”
Section: Activation Of Smads By the Receptor Complexesmentioning
confidence: 99%
“…1 C). ERB IN is known to form protein scaffolds and can complex with SMAD2/3, sequestering it in the cytoplasm, thus preventing transcriptional activity in a manner similar to that seen with STAT3C overexpression in vitro (Sflomos et al, 2011;Wang et al, 2016). Using gel filtration chromatography, we identified a large molecular weight fraction containing SMAD2/3, STAT3, and ERB IN and that contained pSMAD2/3 after STAT3 activation by IL-6 ( Fig.…”
Section: Introductionmentioning
confidence: 90%